Sosialisasi Penggunaan Lubang Biopori Dalam Rangka Mengurangi Banjir Di SMP Negeri 3 Cikarang Timur - Istianah Setyaningsih; Yenia Endriastuti (Institut Ilmu Sosial dan Manajemen Stiami, 2018)
Bekasi Regency, one of the districts affected when rainfall is high occurs according to data from BPS during 2016 the average rainfall reached 2,000.12 mm. Public Middle School 3 East Cikarang, one of the areas that has the potential for flooding, is caused by a lower land surface than the surrounding area. Biopori Infiltration Hole, is one of the techniques carried out for disaster mitigation and can be applied easily by everyone. The purpose of this study is to find out how much the benefits of biopori as a solution to minimize the potential for flooding applied in schools that are often affected by flooding. The benefit of this research is that students and the community know the benefits of biopori as a whole, not just as a flood prevention. The results obtained are overall knowledge about biopori, the benefits of applying biopori, designing a good biopori installation location, and also designing an effective biopori manufacture.